Pengelolaan Manajemen Usaha Produk Kecantikan Sebagai Upaya Mencapai Kemandirian Finansial - Arief Yuswanto Nugroho; Ari Nurcahyo Darmawan; Sari Sukmawati; Putri Laila Maysaroh Angkat; Deys Novanda Veronica; Mohamad Aris Kurniawan (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
Every business activity must have a goal, and theirs is to be successful, advance and build the business, and become financially independent. A firm needs effective management to make it easier for it to succeed; in this instance, solid finances and fulfilling all of the company’s financial demands are necessary in order to get the desired outcomes. By having separate finances in a firm, effective and efficient management may make a company balanced in achieving goals for the sake of shared prosperity.In order to manage and steer an organization and ensure that the management process is well-structured, management science is crucial. We may be confident that a firm will succeed and be effectively executed if its goals are met in accordance with the anticipated strategy. A business’s healthy finances serve as proof of this.